ANALISIS KAUSALITAS ANTARA CAPITAL INFLOW DAN NILAI TUKAR RUPIAH DI INDONESIA - Dina Octaria; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2013)
This study aims to know whether there is a significant interrelationship between the Capital Inflo and the Kurs a Exchange Rate in Indonesia. The test is carried out using Stationarity Test, Kointegrasi Test, Granger Causality Test, and Vector Error Correction Model (VECM) test for the period 2004 I – 2012 IV. Cointegration test result indicate that the relationship between Capital Inflow and Kurs a Exchange Rate in Indonesia has a long-term equilibrium relationship. Granger Causality test result revealed that there is a direct relationship the Kurs a Exhange Rate affect the Capital Inflow. Based on the result of impluse Response Function, it was found that the Capital Inflow has a negative effect on the Rupiah, similarly the Rupiah has a negative effect on the Capital Inflow. While the result of variance decomposition showed that the role of Capital Inflow and the Rupiah is significant.Keywords : Capital Inflow, The Rupiah, Granger Causality, VECM.